Comparison of Age-Related Hearing Loss in Diabetics and Non-Diabetics Patients - Nader Saki (Journal of Global Pharma Technology, 2017)
Background and Objectives Presbycusis refers to symmetrical and bilateral hearing loss which occurs with aging. Diabetes mellitus affects multiple systems of the body and causes conditions that are often irreversible. The aim of this study was to compare age-related hearing loss in diabetic patients and non-diabetics. Methods & Materials In this study, 42 diabetic patients who visited the Diabetes Center of Ahvaz were randomly selected. Forty-two non-diabetics who visited the otolaryngology center not complaining of hearing problems were randomly selected as the control group. Audiometry (AZ26 interacoustic Co. Denmark) is done for all subjects. Independent t-test was used to compare the two groups. The Mann-Whitney test was used for ordinal variables, while the chi-square test was used for qualitative variables. The analyses were conducted using SPSS version 20 Results The findings showed an increased prevalence of hearing loss in patients with diabetes. The bilateral hearing loss was observed in both diabetics and non-diabetics but its prevalence was significantly higher in the diabetic group (P value<0.05). Conclusion Hearing loss was more prevalent in diabetics than non-diabetics, while hearing thresholds were affected in all frequencies of audiometry.Keywords: Diabetes; Age-related hearing loss; Presbycusis; Audiometry.